Corporate Philanthropy and Corporate Perceptions of Local NGOs in Vietnam - Giang Dang; Pham Minh Tri; Giang Dang; Pham Minh Tri (LUCK HOUSE GRAPHICS LTD)
The study aims to establish a baseline of corporate philanthropy in Vietnam based on a random sample of over 500 Vietnamese companies, complemented by a dozen in-depth interviews in Ha Noi, Da Nang and Ho Chi Minh City.